From Experience to Policy: Lessons Learned from Vientiane–Vang Vieng Expressway Management for the Development of the Vang Vieng–Luang Prabang–Natuey Expressway - Lounbandith, Nouphit; Sylilertmany, Khamkeo; Lattanasouvannaphonh, Champa; Xayavong, Somkuan; Vongthongchit, Ken (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study analyzes management experiences from the Vientiane–Vang Vieng expressway to derive policy lessons for the development of the forthcoming Vang Vieng–Luang Prabang–Natuey expressway. Drawing from the literature on public–private partnerships (PPP), risk management, social safeguards, institutional capacity, and regional integration, the paper identifies key issues observed during implementation financial risks, institutional gaps, insufficient community engagement, operational limitations, and road safety concerns. The study proposes policy recommendations for the next expressway phase, emphasizing strengthened project appraisal, enhanced regulation, improved resettlement practices, service development, safety measures, economic integration, and transparent governance. Lessons from the first phase underscore the need for systematic planning and inclusive development to ensure sustainable expressway management in Laos.